Recurrent cardiac intimal sarcoma misdiagnosed as a myxoma or malignant transformation of a cardiac myxoma?. Issue 1 (22nd November 2020) - Durieux, Rodolphe; Tchana‐Sato, Vincent; Lavigne, Jean‐Paul; Radermecker, Marc A.; Moonen, Marie; Scagnol, Irène; Gennigens, Christine; Defraigne, Jean‐Olivier
Abstract: Cardiac intimal sarcoma is extremely rare and aggressive primary malignant cardiac tumors. Here, we reported the case of a young man initially operated for a tumor of the left atrium, causing a dynamic obstruction of the mitral valve and (mis‐)diagnosed as a myxoma at the histopathological analysis. Patient presented a local recurrence at 3 months and was reoperated. Pathology revealed this time the presence of an intimal sarcoma. Patient received adjuvant chemotherapy. Despite a good local control, the 1‐year follow‐up positron emission tomography scan revealed the presence of a metastasis in the left adrenal gland that was surgically resected. This article aims to highlight the risk of misdiagnosis in case of cardiac tumors, the hypothetical concept of malignant transformation of a cardiac myxoma, the aggressive course of the extremely rare cardiac intimal sarcoma, and the therapeutic modalities available to treat this pathology.